VDR gene variants FokI and ApaI: Factors associated with susceptibility to multiple sclerosis - Laith AL-Eitan; Salma Darabseh (PLoS ONE, 2025)
Multiple Sclerosis (MS) is a commonly observed autoimmune inflammatory condition that affects the central nervous system (CNS). Vitamin D functions as a steroid hormone by interacting with its nuclear receptor, the vitamin D receptor (VDR), to regulate critical biological processes. The polymorphisms of the VDR gene have not yet been investigated in the cohort of MS patients in Jordan. We aimed to examine the genetic associations between polymorphisms in the VDR gene (specifically, TaqI, BsmI, ApaI, and FokI) and susceptibility to Multiple Sclerosis (MS). Additionally, we aimed to investigate the relationship between vitamin D status and VDR gene polymorphisms in relation to the onset of MS in Jordanian individuals. The study cohort included 218 individuals diagnosed with Multiple Sclerosis (MS) and 200 healthy controls. The Sequenom MassARRAY system was used for genotyping all single-nucleotide polymorphisms (SNPs). The findings reveal a significant correlation, indicating an increased risk of multiple sclerosis associated with FokI (P = 0.03) and ApaI (P = 0.04), contrasting with the findings for BsmI and TaqI. Only the FokI SNP has been significantly linked (P = 0.03) to a clinical phenotype of multiple sclerosis: vitamin D deficiency. While the cross-sectional nature of the study limits causal interpretations, the results highlight the potential role of the Vitamin D Receptor gene in MS susceptibility. Further studies on gene-environment interactions should be conducted in a distinct population of Arab descent to strengthen and validate the genetic link between VDR and MS susceptibility.